Efektivitas Arduino Sebagai Penerima Data Melalui Level Shifter Digital Caliper Guna Rancang Bangun Alat Ukur Ketebalan Ban - Yoshio Sudewa; Andi Widiyanto; Setiya Nugroho (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
This research was carried out by modifying a tool for measuring thickness so that the data received can be displayed on a serial monitor. In this case, the researcher modified the digital caliper or existing tool to integrate with the Arduino by means of a level shifter to increase the voltage current of the digital caliper so that the Arduino could read the data received according to its compatibility. The value obtained with the Arduino utilizes the data pin and clock pin on the digital caliper which have been connected to the pins available in the level shifter. After the data is processed by the Arduino, the data will then be sent to the microcontroller, then the value will be displayed in the serial monitor. The experimental method used is to send data to the Arduino according to the values in the LCD display available in the measuring instrument or tire depth. The treatment consists of providing tire depth variation values on a millimeter scale from 00.00 millimeters to 18.00 millimeters. Experimental results on measurements show that the values obtained by Arduino and measuring instruments are not much different.